2017 IEEE 28th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2017
DOI: 10.1109/pimrc.2017.8292557
|View full text |Cite
|
Sign up to set email alerts
|

On the integration of LoRaWAN with the 5G test network

Abstract: The major focus of the low power wide area networks (LPWAN) is to provide energy efficiency and large coverage to Internet of Things (IoT) applications that do not require a large bandwidth. There are several LPWAN technologies that can enable these functionalities such as SigFox, LoRa Wide Area Network (LoRaWAN), Narrowband-IoT (NB-IoT), and Weightless. The estimates of the number of wireless IoT devices in the near future are between 20 Billion to even 75 Billion. At the very same time the development and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…The distance from the gateway to the nearest point of the target deployment area is approximately 180 m. The gateway was configured to use the default frequency plan, including the three default LoRaWAN channels. A special application has been deployed on top of the gateway to forward the collected sensor data to the ThingWorx IoT platform [16], which stored all the collected data, over MQTT protocol (for further details refer to [11]). Using few test devices, we characterized the performance of the communication for the different SF/DR between a test device located in the various points in the test area.…”
Section: Network Deployment and Configurationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distance from the gateway to the nearest point of the target deployment area is approximately 180 m. The gateway was configured to use the default frequency plan, including the three default LoRaWAN channels. A special application has been deployed on top of the gateway to forward the collected sensor data to the ThingWorx IoT platform [16], which stored all the collected data, over MQTT protocol (for further details refer to [11]). Using few test devices, we characterized the performance of the communication for the different SF/DR between a test device located in the various points in the test area.…”
Section: Network Deployment and Configurationsmentioning
confidence: 99%
“…1. The packet flow from sensor network to application interface, technical details and challenges are available in [11].…”
Section: Network Deployment and Configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that, in this case, LPWANs are not intended to substitute 4G and 5G networks, where available. Indeed, some studies exploiting the possible integration of LPWAN solutions with 5G system have been already presented in the literature [48,49]. In particular, it has been demonstrated that LPWANs can be used as viable complement to existing solutions when the refresh time interval is relatively long (on the order of 1 min), and when low throughput values (on the order of 1 kb/s) are tolerated.…”
Section: The Communication Infrastructurementioning
confidence: 99%
“…It has to highlight that mobile communications, despite partially overlap with LPWAN target scenarios, are an ideal complement and, especially when 5G systems will be available, could be used for implementing the backbone of a wireless multi-tier approach. In some papers, such possible integration has been discussed [42,43].…”
mentioning
confidence: 99%